Crime and punishment in Latin America law and society since late colonial times - Salvatore, Ricardo Donato; Aguirre, Carlos 1958-; Joseph, G. M. 1947- (Duke University Press, 2001)
Introduction: writing the history of law, crime, and punishment in Latin America / Carlos Aguirre and Ricardo D. Salvatore -- Crime in the time of the great fear: Indians and the state in the Peruvian Southern Andes / Charles F. Walker -- Women, order, and progress in Guzmán Blanco's Venezuela, 1870-1888 / Arlene J. Díaz -- Judges, lawyers, and farmers: uses of justice and the circulation of law in rural Buenos Aires, 1900-1940 / Juan Manuel R. Palacio -- Work, property, and the negotiation of rights in the Brazilian cane fields: Campos, Rio de Janeiro, 1930-1950 / Luis A. González -- The criminalization of the syphilitic body: prostitutes, health crimes, and society in Mexico City, 1867-1930 / Christina Rivera-Garza -- Healing and mischief: witchcraft in Brazilian law and literature, 1890-1922 / Dain Borges -- Passion, perversity, and the pace of justice in Argentina at the turn of the last century / Kristin Ruggiero -- Cuidado con los rateros: the making of criminals in modern Mexico City / Pablo Piccato -- The penalties of freedom: punishment in post-emancipation Jamaica / Diana Paton -- Death and liberalism: capital punishment after the fall of Rosas / Ricardo D. Salvatore -- Disputed views of incarceration in Lima, 1890-1930: the prisoners' agenda for prison reform / Carlos Aguirre -- Girls in prison: the role of the Buenos Aires Casa Correccional de Mujeres as an institution for child rescue, 1890-1940 / Donna J. Guy -- Remembering freedom: life as seen from the prison cell (Buenos Aires Province, 1930-1950) / Lila M. Caimari -- Afterword: law and society in comparative perspective / Douglas Hay
Includes bibliographical references and index
Keywords: Crime / History / Latin America; Justice, Administration of / History / Latin America; Punishment / History / Latin America